2014
DOI: 10.1038/nri3712
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells, monocytes and macrophages: a unified nomenclature based on ontogeny

Abstract: The mononuclear phagocyte system (MPS) has historically been categorized into monocytes, dendritic cells and macrophages on the basis of functional and phenotypical characteristics. However, considering that these characteristics are often overlapping, the distinction between and classification of these cell types has been challenging. In this Opinion article, we propose a unified nomenclature for the MPS. We suggest that these cells can be classified primarily by their ontogeny and secondarily by their locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
1,437
3
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,512 publications
(1,529 citation statements)
references
References 137 publications
24
1,437
3
14
Order By: Relevance
“…[1][2][3] DCs are represented by two major lineages, classical or conventional DCs (cDCs) and plasmacytoid DCs (pDCs). [1][2][3] cDCs have outstanding capacity to prime naive T cells to generate various types of effector T (T eff ) cells owing to the prominent expression of major histocompatibility complex class (MHC) II and costimulatory molecues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] DCs are represented by two major lineages, classical or conventional DCs (cDCs) and plasmacytoid DCs (pDCs). [1][2][3] cDCs have outstanding capacity to prime naive T cells to generate various types of effector T (T eff ) cells owing to the prominent expression of major histocompatibility complex class (MHC) II and costimulatory molecues.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] DCs are represented by two major lineages, classical or conventional DCs (cDCs) and plasmacytoid DCs (pDCs). [1][2][3] cDCs have outstanding capacity to prime naive T cells to generate various types of effector T (T eff ) cells owing to the prominent expression of major histocompatibility complex class (MHC) II and costimulatory molecues. [4][5][6] On the other hand, pDCs are specialized in endosomal TLR7/9-mediated recognition of viral nucleic acids (NAs) and respond with the massive secretion of type I interferon (IFN-I).…”
Section: Introductionmentioning
confidence: 99%
“…27 Although the DNFB ear irritation model is not a macrophage-specific model, macrophages incorporated from the bloodstream play a critical role in the early stages of this inflammation as well as in its resolution. 17 Mice were treated on the right ear with DNFB and on the left ear with acetone (control) and were euthanized after 7 days. Ears were punched at the inflammatory loci, the punch was weighed, and tissue was collected for histology and RNA extraction.…”
Section: Nbs1 Is Required For M-csf-dependent Proliferation In Macropmentioning
confidence: 99%
“…[14][15][16] Recently, it has been found that when an inflammation is produced, Ly6C high monocytes are released by the bone marrow (BM) to fight pathogenic intruders at inflammatory loci throughout the body. 17 Macrophages may experience DSBs during the proliferation and also during activation, because they are the major producer of NO and ROS that can induce these and other lesions. 18 This suggests that the proper control of DNA damage repair and proliferation is likely to be important in macrophages 19 and could be affected by mutations in the MRE11 complex.…”
Section: Introductionmentioning
confidence: 99%
“…Such DC are phenotypically and ontogenically distinct from monocyte‐derived, redifferentiated in vivo moDC that originate from the committed monocyte progenitor36, 42, 43 (Fig. 1).…”
Section: Vd3 and DC Precursor (Pre‐dc) Derived Dc In The Mousementioning
confidence: 99%